Implementasi Budaya THK dalam Pengaruh Komitmen OPD dan Partisipasi Masyarakat pada Akuntabilitas Pengelolaan Dana Desa - Utari, Ni Wayan Desi Putri; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 28 No 3 (2019), 2019)
This research aims to examine the implementation of Tri Hita Karana (THK) culture in moderating the influence of the commitment of village government organizations (OPD) and community participation on the accountability of village fund management in Kubu Sub-District, Karangasem Regency. The sampling method used is the census method. The respondents used were 36 people. Research data is analyzed using Moderated Regression Analysis (MRA). The results of the study indicate that OPD commitment and community participation gave a positive influence on the accountability of village fund management. The implementation of THK culture strengthens the influence of OPD commitment and community participation on the accountability of village fund management. Keywords : OPD commitment, Community participation, THK culture, Accountability.